Spatially Smoothed Second Order DOA Estimator for Correlated Signals in the Presence of Correlated Antenna Noises - Rhee, Ill-Keun; Kim, Hee-Soo; Lee, Hun-Jong (Computer Applications for Communication, Networking, and Digital Contents, 2012)
An array signal processing methodologies can provide the high resolution of a signal direction of arrival (DOA) estimation, thanks to their conceptual increase of signal-to-noise ratio (S/N). Exploring the eigen-structure based algorithms such as MUSIC, Root MUSIC, etc, gives efficient DOA results when the multiple signals are incoherent. A class of Spatial Smoothing (SS) algorithms spatially break the correlation of coherent signals using spatially distributed overlapping sub-arrays. On the other hand, Second Order (SO) algorithm has been proven to de-correlate correlated antenna noises with known or estimated noise correlation coefficients. In this paper, Spatially SmoothedSecond Order (SS-SO) algorithm, which is made by combining SS algorithm with SO technique, is proposed to resolve efficiently correlated multiple signals in the environment of correlated noise fields. Furthermore, the simulations are performed and analyzed to show that the proposed algorithm gives robust DOA results in several aspects.